DETERMINANTS OF STUDENT DEVIANT BEHAVIOR - Е.М. Ranhyelova (Academy of Cognitive and Natural Sciences, 2022)
This article is devoted to deviative conduct of pupils. The author finds out direct and indirect causes of giving phenomena.